2019
DOI: 10.1016/j.heliyon.2019.e01416
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable water hyacinth cellulose-graft-poly(ammonium acrylate-co-acrylic acid) polymer hydrogel for potential agricultural application

Abstract: Swollen cellulose fibres isolated from water hyacinth were utilized in the synthesis of water hyacinth cellulose-graft-poly(ammonium acrylate-co-acrylic acid) polymer hydrogel (PHG). Acrylic acid (AA) partially neutralized with NH 3 was heterogeneously grafted onto swollen cellulose by radical polymerization reaction using N,N -methylene- bis -acrylamide (MBA) as the cross-linker and ammonium persulphate (APS) as the initiator. The reaction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Among them, primary -OH at C-6 and two secondary ones at C-2 and C-3 can take part in typical reactions such as esterification, etherification, and oxidation. Cellulose derivatives have been obtained by reacting to some (or all) -OH groups of anhydroglucose units [6,7]. Carboxymethylation of cellulose is a common conversion process which provides versatile water-swellable or water-soluble polymers and intermediates with variable characteristics [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, primary -OH at C-6 and two secondary ones at C-2 and C-3 can take part in typical reactions such as esterification, etherification, and oxidation. Cellulose derivatives have been obtained by reacting to some (or all) -OH groups of anhydroglucose units [6,7]. Carboxymethylation of cellulose is a common conversion process which provides versatile water-swellable or water-soluble polymers and intermediates with variable characteristics [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the investigation in this matter is very limited. Among the few studies reported, the use of polymer hydrogels as a network structure, to delay the mineral release and decrease evaporation losses, has been described [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the GS increases as DN decreases at high AA and cassava starch concentration (i.e., 30% AA and 10% cassava starch) (Figure 3c,d). This result could be attributed to the higher degree of crosslinking and copolymerization of AA onto starch produced at lower DN and higher concentration of reactants, which adds to the overall structural integrity of the gel 19,32–34 …”
Section: Resultsmentioning
confidence: 99%